Impact of Natural and Anthropogenic Disturbances on Orthopteran Community in Kaziranga National Park, Assam, India - Senthilkumar, N.; Barthakur, Nizara D. (Indian Forester, 2013)
Impact of natural and anthropogenic disturbance on orthopteran assemblage under grasslands and forestlands in Kaziranga National Park, Assam was studied using BACI (Before-After-control-Impact) method. The study showed that there is a change in the assemblage of orthopterans in the disturbed sites due to natural (flood) and anthropogenic (corridor-road) disturbances in grasslands and forestlands, respectively. Though there is a reduction in the population of orthopteran species after a heavy rainfall, changes in the assemblage of orthopteran community in the disturbed site were in significant. However, in case of forestland frequently disturbed (corridor-road) due to movement of automobiles, the population remain fragmented.